The Effects of Conformation and Intermolecular Hydrogen Bonding on the Structure and IR Spectra of Flutamide; A Study Based on the Matrix Isolation Technique, Ab Initio and DFT Calculations - Arman, C.; Balcı, K.; Akkaya, Y.; AKYÜZ, SEVİM; Reaves-Mckee, T.; Frankamp, ​​AH; Coates, JT; Collier, WB; Ritzhaupt, G.; Klehm, CE; Desman, P. (Pergamon-Elsevier Science Ltd., 2023)
In this study, stable conformers of flutamide referred to as an anticancer drug were searched through a relaxed potential energy surface scan carried out at the B3LYP/6-31G(d) level of theory. This was followed by geometry optimization and thermochemistry calculations performed with the HF-SCF, MP2, B3LYP methods and the 6-31G (d), 6-311++G(d,p), aug-cc-pvTZ basis sets for each of the determined minimum energy conformers. The results revealed that flutamide has at least five stable conformers and two of them provide the major contribution to the observed matrix isolation infrared (IR) spectra of the molecule. The effects of conformational variety and intermolecular hydrogen bonding interactions on the observed IR spectra of flutamide were interpreted in the light of the vibrational spectral data obtained for the most stable monomer and dimer forms of the molecule at the same levels of theory. Pulay's "Scaled Quantum Mechanical-Force Field (SQM-FF)" method was used in the refinement of the calculated harmonic wavenumbers, IR intensities and potential energy distributions. This scaling method which proved its superiority to both anharmonic frequency calculations and other scaling methods helped us to correctly interpret the remarkable differences between the matrix IR spectra of flutamide in argon and the condensed phase IR spectra of the molecule in solvents such as KBr, H2O, D2O, ethanol and methanol.
Keywords: Flutamide; Anticancer Drug; Matrix Isolation; IR Spectra; SQM-FF Method; DFT Calculations